Mechanical, water absorption and tribological properties of epoxy composites filled with waste eggshell and fish scale particles - Behera S.; Gautam R.K.; Mohan S.; Tiwari A. (My University, 2025)
Egg shells and fish scales are two abundantly available by-products from food industries which can be used as filler materials to reinforce polymer composites. The bulk of discarded chicken eggshells and fish scales are disposed of in landfills, which cause environmental issues. The present research work focuses on the water absorption, mechanical and tribological properties of epoxy composites reinforced with chicken eggshells and catla fish scale particles. Hybrid composites incorporating both fillers were also made and evaluated. Results from the water absorption tests showed that the addition of fillers decreased the water absorption of the composites than neat epoxy. Tensile and impact tests revealed that the inclusion of fillers reduced the tensile and impact strength of the composites compared to neat epoxy, but improved the tensile modulus. The hybrid composite (EFREC) showed improvement in both flexural strength and modulus in comparison to neat epoxy. Also, the results from the wear tests revealed that the addition of fillers improved the wear resistance of the composites. Among all the mechanical and wear tested composite specimens, the hybrid composite (EFREC) showed the best performance. This was also validated from the SEM images of the fracture and wear surfaces of the composites. © The Author(s) 2023.